2003
DOI: 10.1021/la034410n
|View full text |Cite
|
Sign up to set email alerts
|

Static Light Scattering Studies on Chitosan Solutions:  From Macromolecular Chains to Colloidal Dispersions

Abstract: The neutralization of a homogeneous series of chitosans with degrees of acetylation (DA) varying between 1% and 71% was followed stepwise by static light scattering. The determination of the gyration radii (R G,z) and the second virial coefficients (A 2) allowed us a better understanding of the chitosan behavior during the neutralization in aqueous solutions. On increasing pH, a critical value was evidenced both by a drop of R G,z and a fall of A 2. The values of the critical pH were also shown as highly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 16 publications
7
122
1
Order By: Relevance
“…We also note that the force-retraction data for the chitosan (FA = 0.01)-mucin interaction at pH 6.9 ( Figure 3c) display unbinding events with a distribution of the AFM-tip-mica surface separations similar to the pH 5.5 case. This particular chitosan is expected not to be soluble in aqueous solution at pH 6.9 [53,54], so a collapsed state of the chitosan close to the anchoring site on the AFM tip with a concomitant reduced accessible stretching could have been envisaged. The fact that we did not observe a force beyond the noise level in stretching the chitosan (FA = 0.01) at pH 6.9 indicates that the required force for extending chitosan under aqueous solution yielding an insoluble state is less than the noise in the employed method (in the order of 5 pN).…”
Section: Mucin-chitosan Forced Unbinding Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also note that the force-retraction data for the chitosan (FA = 0.01)-mucin interaction at pH 6.9 ( Figure 3c) display unbinding events with a distribution of the AFM-tip-mica surface separations similar to the pH 5.5 case. This particular chitosan is expected not to be soluble in aqueous solution at pH 6.9 [53,54], so a collapsed state of the chitosan close to the anchoring site on the AFM tip with a concomitant reduced accessible stretching could have been envisaged. The fact that we did not observe a force beyond the noise level in stretching the chitosan (FA = 0.01) at pH 6.9 indicates that the required force for extending chitosan under aqueous solution yielding an insoluble state is less than the noise in the employed method (in the order of 5 pN).…”
Section: Mucin-chitosan Forced Unbinding Curvesmentioning
confidence: 99%
“…Figure 1 depicts an overview of the strategy applied. Two chitosans with different degrees of acetylation were employed to explore the effect of the pH-dependent solubility of the chitosan molecules [53,54] on their interaction with mucins. Two alginates with different fractions of guluronic acid representing the variety of alginate chemical structures utilized in pharmaceutical applications were selected for this study of interaction capacity with mucin.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic light scattering and static light scattering are useful methods for the characterization of chitosan in solution (Kjøniksen, Iversen, Nystro¨m, Nakken, & Palmgren, 1998;Pa & Yu, 2001;Schatz, Pichot, Delair, Viton, & Domard, 2003;Sorlier, Rochas, Morfin, Viton, & Domard, 2003). With these methods, we can determine the M w of a chitosan sample; therefore, we must have the values of refractive index increment (dn/dC), which can be obtained by differential refractometry (Domard & Rinaudo, 1983;Kasaai et al, 2000).…”
Section: Light Scatteringmentioning
confidence: 99%
“…The proportion of CS between acetylated and nonacetylated residues is responsible for the balance between hydrophilic and hydrophobic interactions. 19 Shi et al 20 and Chen et al 21 have concluded that CS molecular chains can form some hydrophobic microdomains because of their selfaggregation behavior. Li et al 22 reported that the structure of CS chains is transformed from stretched chains into coils and further transformed into intertwisted coils with hydrophobic microdomains coming into being in the intertwisted coils with further increase in concentration during the aggregation process, and the macromolecule structure of intertwisted coils becomes compact and the movement of the macromolecule is restricted.…”
Section: The Formation Mechanism Of Ms Nanoparticals In Csmentioning
confidence: 99%